Business and society in the Middle East : exploring responsible business practice - Azoury, Nehme (Palgrave Macmillan, 2017)
Bridging business and modern Mediterranean practices, this book combines cutting edge contributions from both academics and practitioners. The Middle East is experiencing unprecedented challenges and it is in this context that the business community can play a game-changing role, turning these challenges into opportunities by factoring in dimensions that are attuned to the needs of their environment and those of their stakeholders. Business and Society in the Middle Eastexplores social strategies for redefining CSR to create sustainable, responsible business.
Includes index.
Keywords: Business ethics -- Middle East.; Middle East.; elektronické knihy; electronic books